Implementation Curriculum Independent Study Use Learning Management System (LMS) - Hermansyah, Sam (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
Objective from article This is study journal about implementation curriculum independent use (Learning Management system) LMS. Article This discussed in a manner qualitative using a literature study from the perspective of critical discourse analysis by reviewing several journals relevant to the topic. The steps taken are (1 ) collecting data from relevant journals (2) analyze reading material from journals and draw conclusions from the topic of independent curriculum implementation using the LMS (Learning Management System). Results From the study in this article, it shows that the implementation of the independent curriculum is related with (Learning Management System )LMS . Implementation on curriculum independent Study done with use (Learning Management System) LMS related to each other.